Erratum: Geometric morphometric analysis of malocclusion on lateral cephalograms in Malaysian population - Woon C.K.; Abu Jamal N.A.; Ilmi Mohd Nooi M.N.; Abdullah S.M.; Ibrahim N.M.; Norman N.H.; Alias A. (Korean Association of Anatomists, 2024)
Indexed by Scopus